(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
There has been a growing recognition of the imperative to transition towards more sustainable practices in the manufacturing sector. Aiming towards sustainable practices, the concepts of circular economy and technological innovation offer promising avenues for achieving sustainability goals. In this context, the aim is to examine the evolving research landscape concerning the integration of circular economy principles and technological innovation toward sustainability in the manufacturing sector. To achieve this objective, bibliometrics were conducted using R-Studio. A dataset of scholarly publications from Scopus and Web of Science was used for bibliometrics and analyzed. To analyze the key bibliographic data such as publication titles, authors, publication years, journal/conference names, keywords, abstracts, citation counts, etc., were extracted from the Scopus and Web of Science databases. This study, with the help of R-Studio/Biblioshiny, summarizes the data in the form of main information of the data, most relevant sources, sources production over time, word cloud, and co-occurrence network in the form of tables and figures as well. The findings of the study reveal a growing interest in integrating circular economy and sustainability with 360 documents from both databases. The key themes identified in this study are Sustainable Development, Performance, Management, Sustainability, and Framework. The main limitation of the study is that it focuses only on two databases and suggests future research with a more analytical and broader dataset. This study is most relevant for research scholars by helping them identify key research areas to explore and for organizations and governments as well by suggesting which areas to focus on more.